2020
DOI: 10.3390/medicina56100514
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA Mutation and Clinical Outcomes in Breast Cancer Patients Focusing on Survival and Failure Patterns: A Long-Term Follow-Up Study of Koreans

Abstract: Background and Objectives: This study aimed to evaluate the effect of a BRCA mutation on survival and failure patterns, focusing on the risk of ipsilateral recurrence and contralateral breast cancer in patients. Materials and Methods: We retrospectively reviewed medical records of 300 patients with breast cancer who underwent genetic screening for BRCA1/2 genes and were treated at Samsung Medical Center between 1 January 2000 and 31 December 2010. Ultimately, clinical outcomes of 273 patients were analyzed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Other studies conducted in France and Switzerland found significantly superior 5‐year DFS of BRCA1 carriers than non‐carriers, but not significant for BRCA2 carriers 43 . In contrast, a study conducted in Korea found significantly inferior 10‐year DFS and more contralateral breast cancer in BRCA1/2 carriers than non‐carriers, but no significant difference in 10‐year OS 44 . Furthermore, a study of Korean patients found that clinical nodal status is the only significant factor associated with DFS, even after adjusting for clinical nodal stage, BRCA status, hormonal receptor status, and Ki‐67.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies conducted in France and Switzerland found significantly superior 5‐year DFS of BRCA1 carriers than non‐carriers, but not significant for BRCA2 carriers 43 . In contrast, a study conducted in Korea found significantly inferior 10‐year DFS and more contralateral breast cancer in BRCA1/2 carriers than non‐carriers, but no significant difference in 10‐year OS 44 . Furthermore, a study of Korean patients found that clinical nodal status is the only significant factor associated with DFS, even after adjusting for clinical nodal stage, BRCA status, hormonal receptor status, and Ki‐67.…”
Section: Discussionmentioning
confidence: 86%
“… 43 In contrast, a study conducted in Korea found significantly inferior 10‐year DFS and more contralateral breast cancer in BRCA1/2 carriers than non‐carriers, but no significant difference in 10‐year OS. 44 Furthermore, a study of Korean patients found that clinical nodal status is the only significant factor associated with DFS, even after adjusting for clinical nodal stage, BRCA status, hormonal receptor status, and Ki‐67. Consistent with these findings, adjusted multivariable analysis in the present study revealed that the only significant factor associated with DFS was the stage at diagnosis, whereas BRCA1/2 carriers had inferior DFS compared with BRCA non‐carriers; however, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate-penetrance variants that confer two- to five-fold increased risks [ 8 ] also contribute to a minority of BC cases. According to epidemiological studies, 15–20% of familial BC cases and less than 5% of all BCs are caused by germline variants in the BRCA1 and BRCA2 genes [ 9 ]. Carriers of pathogenic or likely pathogenic variants (PVs) in these genes have a 60–85% risk of developing BC by the age of 70 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%